Iscemic Stroke and Severe Acute Respiratory Distress Syndrom In a Patient Confirmed Positive Coronavirus Disease: Case Report - I Gede Catur Wira Natanagara; Ahmad Irfan; Nurul Rakhmawati; Efriadi Ismail (Syntax Corporation, 2022)
The corona virus infection disease has become a pandemic for almost the last two years that has occurred in all countries including Indonesia. Covid 19 in its development can cause various complications, one of which is the occurrence of neurological disorders in addition to respiratory disorders. One of these neurological complications is stroke. In this case report, we will report a case of a patient who was confirmed positive for Covid 19 with complications of ischemic stroke at the Covid 19 Emergency Hospital Wisma Atlet Kemayoran. A 50-year-old male patient came confirmed positive for Covid 19 to the RSDC Wisma Atlet Kemarayoran. The patient came with a cough since 5 days before going to the ER and was treated using HFNC and was intubated while in the ICU, the patient had decreased consciousness, weakness in the left extremity and seizures. The patient also had a history of hypertension and type II diabetes mellitus. Results Chest X-ray showed bilateral pneumonia and CT scan of the head showed right hemisphere infarction. The pathophysiology of stroke in Covid 19 is due to hyperactivation of inflammatory factors caused by systemic inflammation. In addition, ischemic stroke in Covid 19 patients can occur due to D-dimer and platelet abnormalities. In addition to respiratory disorders, Covid 19 can also cause neurological disorders that can increase morbidity in patients who suffer from it.